Local differences in the position of the mental foramen - Yeşilyurt, H.; Aydinlio?lu, A.; Kavakli, A.; Ekinci, N.; Ero?lu, C.; Hacialio?ullari, M.; Diyarbakirli, S. (My University, 2008)
The mental foramen has been reported to vary in position in different ethnic groups. Repeated failures during injections and operative procedures involving the mental foramen suggest the presence of local differences in a given population. The aim of the present study was to investigate possible local differences of the mental foramen in Eastern Anatolian individuals in the Turkish population. The present investigation is based on the examination of 70 adult mandibles. The study consisted of three measurements, to include the relations of the mental foramen to the following: 1) the lower teeth; 2) the body of mandible; 3) the mandibular symphysis and posterior border of the remus of the mandible. The most common position of the foramen was in line with the longitudinal axis of the second premolar tooth (relation IV), at the midpoint of the mandibular body height and at 1/3.5 of the distance from the mandibular symphysis to the posterior border of the ramus. Local differences of the mental foramen may occur in a population. Prior to surgery knowledge of the most common location of the foramen peculiar to a local population may enable effective mental block anaesthesia to be provided. Copyright © 2008 Via Medica.
Keywords: Mandible; Mental foramen; Mental nerve; Premolar